Law on Cyberbullying in Indonesia, Malaysia, and Brunei Darusallam - Siti Khairunnissa (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
All state have various laws that might apply to bullying behaviors. However, this law shows unintended. This study shows legal analysis in some journal, acts, and regulation in every state. Law Journals were conducted. It examines laws and policies dealing with cyberbullying in Indonesia, Malaysia and Brunei Darussalam starting with defining cyberbullying and then comparing the measures in which the issues surrounding cyberbullying have been addressed using various legal strategies.As of August 2017, 48 states had electronic harassment laws which explicitly included cyber bullying in US State. A total of 44 states included criminal sanctions in their cyber bullying laws. The authors point out that the majority of U.S. states have written legislation to address bullying and cyberbullying and that many state legislation that prohibit electronic bullying and developed consequences for doing so. This study was conducted to gain insight into how cyberbullying law implemented in Indonesia, Malaysia, and Brunei Darussalm.Last, after analyzing existing legislative methods an cyberbullying cases around the world, this article concludes with legal and policy recommendations based on these comparisons in Indonesia, Malaysia, and Brunei Darusallam.